Amish Quilts : Crafting an American Icon - Smucker, Janneken (Book collections on Project MUSE., 2013)
Quilts have become a cherished symbol of Amish craftmanship and the beauty of the simple life. Country stores in Lancaster County, Pennsylvania, and other tourist regions display row after row of handcrafted quilts a favorite souvenir for tourists and a source of income for the quilters, In luxury homes, office buildings, and museums, the quilts have been preserved and displayed as priceless artifacts, they are even pictured on collectible stamps.